Pengaruh Kualitas Sistem dan Beban Kerja Terhadap Kinerja Karyawan pada Pengguna Sistem Pemerintahan Berbasis Elektronik - Muhammad Luky Rauuf; Sutrisno; Ira Setiawati (Yayasan Al Ma'arif Dawuhan, 2024)
This study examines the influence of system quality and workload on employee performance among users of the Electronic-Based Government System (SPBE) at BBPMP in Central Java Province. The research targets all SPBE users, employing a saturated sampling technique with 218 respondents. Using a quantitative approach and multiple linear regression analysis, the study reveals that system quality significantly enhances employee performance, as indicated by a coefficient value (B) of 0.472, t = 16.918, and p < 0.000. Similarly, workload is found to significantly impact employee performance, with a coefficient value (B) of 0.853, t = 14.757, and p < 0.000. These findings suggest that improving system quality and managing workload are critical in optimizing employee performance. System quality, as a key determinant, highlights the importance of robust and efficient systems in facilitating employee tasks, while workload management underscores the balance between task demands and employee capacity. This research contributes to the literature on electronic government systems by providing empirical evidence on factors influencing employee performance, particularly in the public sector context. The insights gained can inform policymakers and organizational leaders in designing and implementing SPBE systems to achieve better outcomes. Future research could explore additional variables such as user satisfaction or training effectiveness to provide a more comprehensive understanding of employee performance determinants.